Academic Supervision in Higher Education: The Case of Government Colleges in Bangladesh (Philosophy and Progress, 2023)
Academic supervision is considered an important mechanism to improve the performance of an educational institution. This article aims to investigate the situation of academic supervision in Bangladeshi Government Colleges (GCs).The article, in particular, explores the impacts of academic supervision on Bangladeshi students and teachers in developing their competencies and confidence in postsecondary educational settings. The study was conducted employing thequalitative research method and collecting data from in-depth interviews, secondary published literature, such as books, journal articles etc. The study finds that effective academic supervision considerably helps students achieve their learning progress as well as teachers attain their professionalization in the GCs of Bangladesh. Various challenges exist in higher education in Bangladesh, which include the lack of resources, limited use of educational tools and technology, policy problems, lack of sufficient training and scope of research for teachers, and so on. This article has made several recommendations for improving academic supervision to enhance quality education in the Bangladeshi GCs.Philosophy and Progress, Vol#71-72; No#1-2; Jan-Dec 2022 P 97-128